Cortical influences drive amyotrophic lateral sclerosis. Issue 11 (14th July 2017) - Eisen, Andrew; Braak, Heiko; Del Tredici, Kelly; Lemon, Roger; Ludolph, Albert C; Kiernan, Matthew C
Abstract : The early motor manifestations of sporadic amyotrophic lateral sclerosis (ALS), while rarely documented, reflect failure of adaptive complex motor skills. The development of these skills correlates with progressive evolution of a direct corticomotoneuronal system that is unique to primates and markedly enhanced in humans. The failure of this system in ALS may translate into the split hand presentation, gait disturbance, split leg syndrome and bulbar symptomatology related to vocalisation and breathing, and possibly diffuse fasciculation, characteristic of ALS. Clinical neurophysiology of the brain employing transcranial magnetic stimulation has convincingly demonstrated a presymptomatic reduction or absence of short interval intracortical inhibition, accompanied by increased intracortical facilitation, indicating cortical hyperexcitability. The hallmark of the TDP-43 pathological signature of sporadic ALS is restricted to cortical areas as well as to subcortical nuclei that are under the direct control of corticofugal projections. This provides anatomical support that the origins of the TDP-43 pathology reside in the cerebral cortex itself, secondarily in corticofugal fibres and the subcortical targets with which they make monosynaptic connections. The latter feature explains the multisystem degeneration that characterises ALS. Consideration of ALS as a primary neurodegenerative disorder of the human brain may incorporate concepts of prion-like spread at synaptic terminals of corticofugal axons. Further, such a concept could explain the recognised widespread imaging abnormalities of the ALS neocortex and the accepted relationship between ALS and frontotemporal dementia.